Toleransi Hidup Umat Beragama (Studi Interaksi Sosial Menuju Integrasi Keagamaan di Mandau) - - Prayugo; Wira Sugiarto; Sahrul Sori Alom Harahap (Akademika: Jurnal Keagamaan dan Pendidikan, 2018)
Social Interaction is a reality that exists in people’s lives; interaction also shows a dynamic change that causes an individual or group to experience change. In Mandau sub district exists several religions, namely Islam, Catholic, Protestant, Konghucu, Buddha, and others. The existence of those religions brings very high tolerance attitude among the societies. Forms of social interaction towards social integration are the main needs in living a peaceful life in a society such as cooperation and accommodation in various fields. The research finding indicates that the social society interaction occurs in Mandau such as in National Holidays and Religious Holidays. Whereas in the field of education shows the integration among the students with different religions in the schools of Mandau sub district.___________________Keywords: Social Interaction, Religious, Integration.